2012
DOI: 10.1016/j.ijdevneu.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

First‐generation neuronal precursors in the crayfish brain are not self‐renewing

Abstract: Adult-born neurons in crayfish (Procambarus clarkii) are the progeny of 1st-generation precursor cells (functionally analogous to neuronal stem cells in vertebrates) that are located in a neurogenic niche on the ventral surface of the brain. The daughters of these precursor cells migrate along the processes of bipolar niche cells to proliferation zones in the cell clusters where the somata of the olfactory interneurons reside. Here they divide again, producing offspring that differentiate into olfactory local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Niche cells, including the 1st-generation neural precursors, are distinctive because they label for glutamine synthetase. The 1st-generation precursors divide in the niche, producing 2nd-generation precursors that migrate along fibrous streams formed by the processes of bipolar niche cells, until they reach proliferation zones in cell cluster 9 or 10 [Benton et al, , 2013 ( fig. 1 ).…”
Section: Adult Neurogenesis In Crayfishmentioning
confidence: 99%
“…Niche cells, including the 1st-generation neural precursors, are distinctive because they label for glutamine synthetase. The 1st-generation precursors divide in the niche, producing 2nd-generation precursors that migrate along fibrous streams formed by the processes of bipolar niche cells, until they reach proliferation zones in cell cluster 9 or 10 [Benton et al, , 2013 ( fig. 1 ).…”
Section: Adult Neurogenesis In Crayfishmentioning
confidence: 99%
“…In a follow-up study, Chaves da Silva et al ( 2012 showed that the anterior proliferation centre is located within the cor frontale , an accessory heart which pumps hemolymph to the brain via the cerebral artery, thus providing a direct link to the neurogenetic niche. In a remarkable cell culture experiment, Benton et al ( 2013 ) succeeded in co-culturing freshly dissected crayfi sh brains with hematocytes that were previously labelled with a vital dye (CellTracker). In the majority of their experiments, labelled hematocytes were taken up in the neurogenetic niche after 6 h of co-cultivation.…”
Section: Life-long Persistent Neurogenesis In the Adult Crustacean Olmentioning
confidence: 99%
“…In the majority of their experiments, labelled hematocytes were taken up in the neurogenetic niche after 6 h of co-cultivation. In summary, Benton et al ( 2013 ) suggested that their experimental evidence shows that the pool of cells within the crayfi sh niche is not selfrenewing but that multipotent stem cells from the hematopoietic tissue are the source replenishing the niche cell pool. In this view, the niche is a system that transforms multipotent blood stem cells into the fi rst-generation neuron precursor cells (review in Sandeman et al 2015 ).…”
Section: Life-long Persistent Neurogenesis In the Adult Crustacean Olmentioning
confidence: 99%
“…Beginning with studies by Harzsch and Dawirs ( 1996b ) and Schmidt ( 1997 ), it is now well known that a life-long generation of new olfactory interneurons that is driven by a persisting neurogenic niche is a characteristic feature of the decapod crustacean central olfactory pathway, and today, this is without question the hottest topic in crayfi sh developmental biology (Beltz and Sandeman 2003 ;Schmidt 2007aSchmidt , b , 2014Sullivan et al 2007a , b ;Beltz et al 2011 ;Sandeman et al 2011Sandeman et al , 2014Benton et al 2013 ). In vivo application of the S-phase-specifi c proliferation marker BrdU showed continuous mitotic activity within a proliferation zone (the lateral proliferation zone) associated with a cluster of olfactory interneurons (cluster 10; terminology of Sandeman et al 1992 ) that persisted from larval into juvenile stages of the brachyuran crab Hyas araneus (Harzsch and Dawirs 1996b ).…”
Section: Life-long Persistent Neurogenesis In the Adult Crustacean Olmentioning
confidence: 99%
“…Noonin et al ( 2012 ) found a specialised region within crayfi sh hematopoietic tissue, the "anterior proliferation centre (APC)", which is located close to the brain and contains multipotent stem cells. In a remarkable cell culture experiment, Benton et al ( 2013 ) succeeded in co-culturing freshly dissected crayfi sh brains with hematocytes that were previously labelled with a vital dye (CellTracker). In a remarkable cell culture experiment, Benton et al ( 2013 ) succeeded in co-culturing freshly dissected crayfi sh brains with hematocytes that were previously labelled with a vital dye (CellTracker).…”
Section: Life-long Persistent Neurogenesis In the Adult Crustacean Olmentioning
confidence: 99%